Design and development of an aptamer targeting C-type lectin-like molecule-1 as a biomarker for acute myeloid leukemia: a SELEX approach - Chen, Yiwen; Li, Qinhang; Lou, Shifeng; Zeng, Hanqing; Chen, Shu (Frontiers in Bioengineering and Biotechnology, 2025)
Acute myeloid leukemia (AML), a hematologic malignancy, is an important public health issue. It is a result of the abnormal proliferation of immature myeloid cells. Despite advancements in diagnostic procedures, the early identification of AML remains a significant clinical challenge, marking a distinctive niche for newer theranostic approaches to ameliorate diagnosis and treatment. Aptamers are single-stranded oligonucleotides capable of specific binding with high target affinity that have emerged as a promising candidate for molecular recognition in diagnostics and targeted therapy. In this study, we aimed to select and characterize a high-affinity aptamer for C-type lectin-like molecule-1 (CLL-1), an important cell surface marker for AML. CLL-1-specific aptamers were enriched in the context of iterative positive and negative rounds of selection in a systematic evolution of ligands by exponential enrichment (SELEX) approach. In the following, flow cytometry assessment demonstrated the progression of enrichment and then confirmed their performance. The high-throughput sequencing supported the enrichment of five candidate aptamers. In addition, flow cytometry and specificity assays determined that aptamer-2 specifically bound to CLL-1 with an exceedingly high degree of specificity (94.3%) compared with negative controls and other aptamers. The surface plasmon resonance (SPR) valuation revealed that aptamer-2 has a Kd of 1.55 × 10−8 M, which indicates a high affinity of binding to CLL-1. Docking analysis reveals a stable and specific interaction between aptamer-2 and CLL-1, highlighting key binding regions and molecular contacts that may underpin targeted recognition. Taken together, the results put forward aptamer-2 as a highly specific and high-affinity candidate for targeting CLL-1. This study opens the prospect of using this aptamer for diagnostic approaches for AML. Further in vivo and translational studies on its efficacy and efficiency are needed to elucidate its performance in real-world scenarios.